PENERAPAN STRATEGI PEMBELAJARAN BEACH BALL UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN STRUKTUR ATOM DI KELAS X SMA NEGERI 1 TANAH MERAH KABUPATEN INDRAGIRI HILIR - Lufi Luthfiyah Wt Lufi Luthfiyah Wt; Maria Erna Maria Erna; Elva Yasmi Amran Elva Yasmi Amran (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract:This research aims to increase student achievement on the subject Atomic Structure in class X SMAN 1 Tanah Merah.  This research is a kind of experiment research with pretest-posttest design. The research was conducted in SMAN 1 Tanah Merah. The samples of this research were the students of class X MIA 2 as the experimental class and  students of class X MIA 3 as  the control class. Experimental class is a class that is applied  learning strategy Beach Ball, while the control class was not. Data analysis technique used is the t-test. Based on analysis of data obtained tarithmetic> ttable is 3,3101 > 1,67, means that the application of learning strategy Beach Ball can improve student achievement on the subject of Atomic Structure in class X SMAN 1 Tanah Merah increase learning achievement category in the experimental class is based on the normalized gain scores (N-Gain) relatively high at 0.7662. Keywords : Learning Achievement, Learning Strategy Beach Ball, and Atomic Structure